Is European integration bad news for developing countries? - POHL, Gerhard (1994)
Claims that the effects of EC-92 on other countries are three-fold: first, the project will change the commercial policy of the EC towards outsiders; second will be indirect economic effects, leading to trade creation and trade diversion from external suppliers to EC firms; and third, the program will affect the commercial policies of third countries, both through direct emulation and through the introduction of single market issues into multilateral trade agreements. Believes that the main effect of the single market program on developing country exports will be from the dynamic gains derived from growth and related structural change beyond the simple trade preferences.